Efektivitas Rambu Batas Kecepatan di Jalan Kolektor - Yulianggi Trisya Pramesti; Anton Budiharjo (Universitas Negeri Gorontalo, 2020)
One of the causes of traffic accidents is the non-compliance of motorized vehicle drivers to comply with the maximum speed limits that have been set. This study discusses and analyzes the effectiveness of the maximum speed limit signs that have been installed on Jalan Perintis Kemerdekaan, Cilacap Regency and provides recommendations for increasing the effectiveness of the maximum speed limit signs. The method used is a direct survey in the field and data analysis of the T-Paired Sample Test, as well as assessing the effectiveness using the N-Gain Score. From the analysis, it was found that the effectiveness of the existing signs was 6.25%. Short-Term Memory is related to what a person thinks when receiving a stimulus from the environment with a storage duration of 15-20 seconds. The storage duration can increase up to 20 minutes if there is repetition of information. To increase the effectiveness of speed limit signs, a simulation of the installation of speed limit signs is carried out repeatedly.